SELF-DEVELOPMENT OF SANTRI THROUGH THE NEW STUDENT ORIENTATION PERIOD (MASTAMA) AT PONDOK PESANTREN DARUL QURAN MOJOKERTO 2026/2027 ACADEMIC YEAR - Hajar Nurma wachidah (LEMBAGA PENELITIAN, PENGABDIAN PADA MASYARAKAT, PENINGKATAN AKTIVITAS INSTRUKSIONAL, PENINGKATAN DAN PENJAMINAN MUTU UNIVERSITAS ISLAM MAJAPAHIT, 2026)
This community engagement program was implemented by Hajar Nurma Wachidah of Universitas Islam Majapahit (UNIM) to foster self-development among newly enrolled students (santri) participating in the New Student Orientation Period (Masa Ta'aruf Santri Baru/MASTAMA) at Pondok Pesantren Darul Quran, an Islamic boarding school in Kota Mojokerto whose vision is to cultivate noble santri character (akhlaqul karimah) through an integrated tahfizh Qur'an and formal-education system, during the 2026/2027 academic year. First, background. The transition from a home environment to a boarding-school setting often triggers adjustment difficulties, homesickness, and diminished self-confidence among new santri, whereas previous studies indicate that structured orientation activities and guidance services can accelerate psychosocial adaptation and independence. Second, methods. The program engaged 96 new santri through five structured MASTAMA modules, self-recognition and motivation, time-management and discipline, leadership and public speaking, peer mentoring, and spiritual strengthening, implemented over fourteen days using a participatory action approach, structured observation, in-depth interviews, and pre-test/post-test self-assessment instruments. Third, results and discussion. Participants exhibited measurable improvement across five self-development indicators independence, self-confidence, discipline, social skills, and learning motivation, corroborating self-efficacy theory (Bandura, 1977) and student-involvement theory (Astin, 1984). Fourth, conclusion. MASTAMA constitutes an effective vehicle for cultivating santri self-development and is recommended for continuous refinement through structured indicators and sustained mentoring beyond the orientation period